Evaluation of Wastewater Pipeline Network Discharge in the Area of Patimura Street to Prapanca Raya Street, South Jakarta - Ali Bahroni; Alizar Alizar (International Journal Multidisciplinary Science, 2026)
This study evaluates and plans a wastewater pipeline network to support sustainable urban wastewater management in the Pattimura Street–Prapanca Raya area. The analysis uses a gravity-flow hydraulic approach that considers domestic wastewater discharge, infiltration, peak factors, and pipe filling conditions. The results indicate that the maximum design discharge of 0.7296 m³/s can be accommodated by the planned pipeline network. The calculated pipe diameter was adjusted to a standard size of 250 mm to ensure sufficient capacity and safe operation. Flow velocities meet technical requirements, preventing sedimentation and pipe damage. An 80% pipe filling ratio provides reserve capacity for future flow increases, while the design discharge remains within the capacity of the existing wastewater treatment plant. Therefore, the proposed wastewater pipeline network is optimally designed and suitable as a connection point for future network development